2016
DOI: 10.1097/mat.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Consequences of Intraaortic Balloon Counterpulsation Versus Left Ventricular Assist Devices at the Time of Heart Transplantation

Abstract: The proportion of heart transplant recipients bridged with durable left ventricular assist devices (dLVADs) has dramatically increased; however, concern exists regarding obligate repeat sternotomy, increase bleeding risk due to anticoagulation and acquired von Willebrand disease, and increased rates of allosensitization. Whether dLVAD patients have impaired post-transplant outcomes compared to equivalent patients with less invasive intraaortic balloon counterpulsation (IABP) at the time of transplant is unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…2 It has on the other hand been suggested that the IABP may be underused as a bridge to transplantation. 3 Clinical trials on acutely ill patients can be challenging, because the nuances of acute management cannot be captured through trial data points. For example, 10% of patients randomized to the control group in the IABP-SHOCK II trial received an IABP within days of randomization but were analyzed within that arm as intention to treat, which may falsely elevate survival rate.…”
mentioning
confidence: 99%
“…2 It has on the other hand been suggested that the IABP may be underused as a bridge to transplantation. 3 Clinical trials on acutely ill patients can be challenging, because the nuances of acute management cannot be captured through trial data points. For example, 10% of patients randomized to the control group in the IABP-SHOCK II trial received an IABP within days of randomization but were analyzed within that arm as intention to treat, which may falsely elevate survival rate.…”
mentioning
confidence: 99%
“…19,20 However, LVADs have been shown to have similar perioperative mortality, length of hospital stay, renal failure requiring dialysis or early acute rejection compared to IABPs in patients undergoing heart transplant. 21 At the time of listing for transplant, patients who underwent IABP support (compared to LVAD) had significantly higher serum creatinine, lower BMI, lower proportion of blood type O and more functional impairment requiring full assistance with activities of daily living. 21 This study suggests that patients who have IABP support are generally more unwell and less mobile, which is likely to further exacerbate patient deconditioning.…”
Section: Intra Aortic Balloon Pumps Versus Left Ventricular Assist Dementioning
confidence: 97%
“…21 At the time of listing for transplant, patients who underwent IABP support (compared to LVAD) had significantly higher serum creatinine, lower BMI, lower proportion of blood type O and more functional impairment requiring full assistance with activities of daily living. 21 This study suggests that patients who have IABP support are generally more unwell and less mobile, which is likely to further exacerbate patient deconditioning. Long-term IABP support has been shown to be effective as a bridge to LVAD implantation in critically ill end-stage CHF patients and was not associated with increased haemorrhagic complications.…”
Section: Intra Aortic Balloon Pumps Versus Left Ventricular Assist Dementioning
confidence: 97%
“…Jennings et al 45 No increase in postoperative mortality after CTX. MCS as BTT Castleberry et al 47 No difference in outcomes between IABP vs LVAD support at time of CTX. Grimm et al 48 Duration of LVAD support did not predict mortality posttransplant.…”
Section: Topic Authors Findingsmentioning
confidence: 99%
“…Literature published in 2016 included 2 studies that addressed this issue. Castleberry et al 47 analyzed data from…”
Section: Mechanical Circulatory Support In Ctxmentioning
confidence: 99%